Evidências de degradação ambiental do Igarapé Beira Rio, Município de Mojuí dos Campos - Pa - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
The present article was originated by the concern with the lack of preservation and awareness regarding the use of the environment, mainly of Igarapé Beira Rio, located in the Center District, in the Municipality of Mojuí dos Campos - PA. This work aims to understand the relationship between the process of expansion of the city of Mojuí dos Campos with natural and anthropic factors that has been changing the environmental characteristics of the main watercourse located in the center of the city, as well as demonstrate what happens with the springs when there is a process of removal of the ciliary forest, in the present case, the Beira Rio stream. It is emphasized that the ciliary forest has a priority role in the stability of the erosive phenomena, as it serves as protection against the impacts of the water droplets. rainfall that falls directly on the soil, if it is devoid of vegetation, causing erosion and consequent silting of the springs. The approach to the problem was qualitative-quantitative. The target audience was the residents who live on the banks of the Beira Rio stream. For the data collection, an interview was conducted with residents using a questionnaire with closed questions. Fieldwork was also carried out to identify processes in the studied area. The analyzes indicate the need for preservation of the Beira Rio spring due to the processes of degradation, mainly by anthropic actions, whether due to negligence or ignorance of the environmental protection law. It is hoped that this work contributes to the local reality, as far as the decision-making regarding the management and conservation of this water resource is concerned, because although this is starting a new mentality about the environment in the municipality, it becomes necessary to make the society to adopt new positions in the face of natural resources.
Keywords: Degradação; Mata ciliar; Manancial; Preservação; CNPQ:: CIÊNCIAS HUMANAS